รัฐธรรมนูญและสถาบันการเมือง : ศึกษารัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2489 และรัฐธรรมนูญแห่งราชอาณาจักรไทย (ฉบับชั่วคราว) พุทธศักราช 2490 - ศุภกาญจน์ ตันตราภรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This master thesis aims to analysis provisions, structure, mechanism, and enforcement of Constitutions of Thailand through the political situation since the end of World War II until the promulgation of the 1947 Constitution. The result of study shows that the 1946 Constitution was drafted and promulgated after the second World War when the military leader, Field Marshall P. Pibulsongkram, lost his political power to civic front. The structure and provisions of such Constitution, for example, the bicameral system, the freedom to form political party, the Constitutional Tribunal indicate the promise for democracy. The provisions also prohibit the civil servant to hold political position which aims at preventing the military to regain their power. This subsequently led to the Coup etat in 1947. It is believed that apart from the disagreement of military from some people in "Free Thai Movement", the dead of King Rama VIII was used by the Coup makers to legitimise the Coup etat. Unprecedentedly, the coup maker repealed the 1946 Constitution and drafted the new one which consequently promulgated as 1947Constitution. The 1947 Constitution established bicameral system to which government is responsible both the King and the Parliament. This is the only case in the political history of Thailand. After the Coup etat, the Coup makers designated the civic front to be government mainly due to the fact that the Coup makers were awared of not being recognised by foreign governments and feared of rumour from the public. The government later on proposed to amend the 1947 Constitution in order to prevent the Coup makers from influencing the new Constitution which is believed to be less democracy. Eventually, the 1949 Constitution came into force and renowed as the most democratic Constitution. The thesis concludes that the formulation of Constitutions in the past was used by the drafters as a mean to secure the power and interest of their own group and at the same time to entail conditions for limiting the political role of the oppositions. Efforts to link up the provisions of constitution with political situation can be seen as one way to ligitimise themselves.